Lysimetric studies for modelling radioactive contaminant transport in soils. (1st January 2013) - Rao, B. Hanumantha; Sridhar, V.; Rakesh, R.R.; Singh, D.N.; Narayan, P.K.; Wattal, P.K.
To assess the movement of contaminants in the soil mass surrounded by near/subsurface waste repository, researchers have developed several mathematical and numerical modelling techniques. However, most of these techniques consider remolded state of soil mass, which fail to reproduce exact in situ conditions and also have used inactive salts as model contaminants. Hence, in order to model transport of radioactive contaminants, in situ lysimetric studies were conducted at a waste disposal site and efforts were made to predict long-term transportation of these contaminants by employing VS2DT software. Results obtained have been critically examined vis-à-vis those obtained from soil coring experiments.